New ultra-high temperature nanoindentation system for operating at up to 1100 °C. (July 2020) - Minnert, Christian; Oliver, Warren C.; Durst, Karsten
Abstract: In this work a new ultra-high temperature (UHT) nanoindentation system for testing at up to 1100 °C is presented. The system is capable to perform indents from small scale up to large indentation depths due to the combination of a 1 N actuator and a frame stiffness of > 1 · 10 6 N m even at 1100 °C. Dynamic testing allows a continuous determination of the contact stiffness (CSM) and thus also the depth-dependent hardness and indentation modulus. Low drift rates can be achieved by an independent tip and sample heating. Operating the nanoindenter inside a scanning electron microscope (SEM) equipped with a high temperature backscattered electron (BSE) detector opens the possibility of in-situ observations, as high vacuum minimizes oxidation effects. The HT capability of the system is demonstrated on three reference materials: fused silica, molybdenum assessing the change in modulus with increasing temperature using constant strain rate tests (CSR). The creep response of single crystalline Ni has been assessed by strain rate jump (SRJ) as well as a step-load and hold creep (SLH) method. The resulting modulus, hardness as well as the strain rate sensitivity from RT up to 1100 °C are in good accordance with literature data, highlighting the applicability of the system. Graphical abstract: Unlabelled Image Highlights: A new high-temperature and in-situ nanoindentation system was developed for testing temperature of up to 1100 °C. The sophisticated temperature management with tip and sample heating as well as actuator cooling leads to low drift rates. The determination of reliable hardness and Young's modulus data was presented by constant strain rate tests on fused silica for T  < 300 °C and Mo for testing up to 1100 °C. The applicability of the system to determine the creep behavior has been shown for single crystalline Ni up to 1100 °C was by using indentation strain rate jump and step load and hold methods.